APLIKASI KASIR PENJUALAN KOPI BERBASIS PHP DENGAN MENGGUNAKAN CODEIGNITER DAN DATABASE MYSQL: Studi Kasus di Burak Kopi - Julpa; Fadzar Rusghana (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The development of science and technology at this time has a very important role, one of which is in the field of computers. which makes computer devices equipped with application programs so that they can be utilized optimally. Along with the development of technology in this era of globalization, it can make it easier for people to carry out learning, education, and other activities because this website-based application program can accelerate information conveyed quickly and precisely. The research method used is to conduct field research in the form of observations and interviews to obtain the data and information needed in the research. The purpose of this discussion is to find out the coffee sales cashier system carried out by Burak Kopi. With the PHP-based coffee sales cashier application using CodeIgniter and MySql database, it is expected to be able to present information thoroughly and accurately and more efficiently than the old system. This coffee sales cashier application at Burak Kopi is to facilitate the transaction process on coffee sales.